2017
DOI: 10.5535/arm.2017.41.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Mobility and Self-Care Activity in Children With Cerebral Palsy

Abstract: ObjectiveTo investigate the factors influencing the development of self-care activity, and the association between mobility and self-care activity in children with cerebral palsy (CP).MethodsA total of 63 CP children aged ≥4 years, were studied retrospectively. Children with severe intellectual disability or behavioral problems were excluded. The relationship between the Gross Motor Function Classification System (GMFCS), the Manual Ability Classification System (MACS), and the Pediatric Evaluation of Disabili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 22 publications
2
25
1
Order By: Relevance
“…45 A previous study 3 asserted that intellectual disability, type of cerebral palsy, and functional level did not account for significant differences between those with and without psychiatric disorders. Conversely, our study confirmed other previous findings 38 that severity of intellectual disability is strongly correlated with hand functions ( P < .001; OR 9.8) and gross motor levels ( P < .001; OR 6.8). We also found a strong association ( P = .01) between profound intellectual disability and epilepsy as previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…45 A previous study 3 asserted that intellectual disability, type of cerebral palsy, and functional level did not account for significant differences between those with and without psychiatric disorders. Conversely, our study confirmed other previous findings 38 that severity of intellectual disability is strongly correlated with hand functions ( P < .001; OR 9.8) and gross motor levels ( P < .001; OR 6.8). We also found a strong association ( P = .01) between profound intellectual disability and epilepsy as previously reported.…”
Section: Discussionsupporting
confidence: 92%
“…The PEDI self-care domain itself is not directly related to mobility. In a previous study, GMFCS levels and PEDI mobility were factors that significantly influenced PEDI self-care in children with CP [36]. Moreover, another study using multivariate analysis indicated that GMFCS and intellectual capacity were the strongest determinants of the development of selfcare activities in children with spastic bilateral and unilateral CP [37].…”
Section: Discussionmentioning
confidence: 85%
“…CYSHCN might be at an increased risk for the development of oral diseases due to their compromised motor, sensory and intellectual abilities [ 26 ]. Maintaining good oral hygiene for CYSHCN is a challenge as they tend to have poor control of lips or tongue, inadequate motor capacity and poor cognitive abilities to understand the importance of oral health [ 27 29 ]. A recent study using data from the 2016–2018 National Survey of Children’s Health (NSCH) in the United States, reported that CYSHCN have poorer oral health compared with non-CYSHCN despite receiving more preventive oral health services [ 30 ].…”
Section: Introductionmentioning
confidence: 99%